The Role of Environmental Education in Enhancing Youth Awareness of the Green Economy for Sustainable Development - Marcia, Sila; Marcelinus, Marcelinus (Cebong Journal, 2025)
This research investigates the role of environmental education in enhancing youth awareness of sustainability and its connection to the green economy. Using a mixed-methods approach combining surveys, interviews, and classroom observations, the study examines how exposure to environmental education influences ecological literacy, sustainable behavior, and understanding of green economy concepts. The findings indicate a strong positive correlation between environmental education exposure and youth awareness, highlighting that integrating themes such as renewable energy, sustainable consumption, and circular economy practices into learning significantly strengthens environmental responsibility and economic understanding. Furthermore, the study identifies effective strategies, including experiential learning, project-based activities, and interdisciplinary approaches, as key drivers of student engagement. Policy recommendations emphasize the need to strengthen environmental education frameworks and systematically integrate green economy concepts into formal curricula. While the research acknowledges challenges such as limited resources, uneven curriculum implementation, and a lack of longitudinal data, it underscores the importance of education as a foundation for cultivating environmentally responsible citizens and preparing future generations to contribute to sustainable economic transformation.